2011
DOI: 10.1007/s12471-011-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Right-sided invasive metastatic thymoma of the heart

Abstract: Cardiac tumours may display diverse symptoms through potential involvement of any structure of the heart. We describe a case of a highly malignant thymoma with involvement of different cardiac structures with important haemodynamic compromise. With the high sensitivity of transthoracic echocardiography for detection of intracardiac masses, computed tomography and magnetic resonance add essential structural preoperative information on the tumour and surrounding tissue as vessels, pleura, lung and mediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Pericardial involvement can lead to effusion and tamponade. 4 Primitive neuroectodermal tumor usually occurs in central and peripheral nervous system or soft tissue and bone, 2 while isolated in the heart is considered as extremely rare. Kath R et al 5 first reported a case of cardiac pPNET, and since then there are no more reports of such cases.…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial involvement can lead to effusion and tamponade. 4 Primitive neuroectodermal tumor usually occurs in central and peripheral nervous system or soft tissue and bone, 2 while isolated in the heart is considered as extremely rare. Kath R et al 5 first reported a case of cardiac pPNET, and since then there are no more reports of such cases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent issues of this journal two cases were published [1, 2]. The incidence was reported between 0.0017 and 0.19 % in an unselected population at autopsy [3].…”
Section: Discussionmentioning
confidence: 99%
“…The heart is regularly involved in metastatic neoplasms [ 1 – 3 ] with cardiac metastases found in 6–20 % of autopsies [ 4 , 5 ]. Malignant melanoma is responsible for 4.4 % of these cardiac metastases; other causes are lymphoma, sarcoma and leukaemia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%